Genetic diversity and susceptibility to Vip3Aa20 protein in Brazilian populations of Helicoverpa armigera and Helicoverpa zea (Lepidoptera: Noctuidae) - Leite, Natália Alves (2016)
Helicoverpa armigera (Hübner) was officially reported in Brazil in 2013. This species is closely related to Helicoverpa zea (Boddie) and has caused significant crop damage in Brazil. The use of genetically modified crops expressing insecticidal protein from Bacillus thuringiensis (Berliner) has been one of the control tactics for managing these pests. Genetically modified maize expressing Vip3Aa20 was approved to commercial use in Brazil in 2009. Understanding the genetic diversity and the susceptibility to B. thuringiensis proteins in H. armigera and H. zea populations in Brazil are crucial for establishing Insect Resistance Management (IRM) programs in Brazil. Therefore, the objectives of this study were: (a) to infer demographic parameters and genetic structure of H. armigera and H. zea Brazil; (b) to assess the intra and interspecific gene flow and genetic diversity of H. armigera and H. zea; and (c) to evaluate the susceptibility to Vip3Aa20 protein in H. armigera and H. zea populations of Brazil. A phylogeographic analysis of field H. armigera and H. zea populations was performed using a partial sequence data from the cytochrome c oxidase I (COI) gene. H. armigera individuals were most prevalent on dicotyledonous hosts and H. zea individuals were most prevalent on maize crops. Both species showed signs of demographic expansion and no genetic structure. High genetic diversity and wide distribution were observed for H. armigera. A joint analysis indicated the presence of Chinese, Indian, and European lineages within the Brazilian populations of H. armigera. In the cross-species amplification study, seven microsatellite loci were amplified; and showed a potential hybrid offspring in natural conditions. Interespecific analyses using the same microsatellite loci with Brazilian H. armigera and H. zea in compare to the USA H. zea were also conducted. When analyses were performed within each species, 10 microsatellites were used for H. armigera, and eight for H. zea. We detected high intraspecific gene flow in populations of H. armigera and H. zea from Brazil and H. zea from the USA. Genetic diversity was similar for both species. However, H. armigera was more similar to H. zea from Brazil than H. zea from the USA and some putative hybrid individuals were found in Brazilian populations.Tthere was low gene flow between Brazilian and USA H. zea. The baseline susceptibility to Vip3Aa20 resulted in low interpopulation variation for H. zea (3-fold) and for H. armigera (5-fold), based on LC50. H. armigera was more tolerant to Vip3Aa20 than H. zea (≈ 40 to 75-fold, based on CL50). The diagnostic concentration for susceptibility monitoring, based on CL99, was fairly high (6,400 ng Vip3Aa20/cm2) for H. zea and not validated for H. armigera due to the high amount of protein needed for bioassays. Implementing IRM strategies to Vip3Aa20 in H. armigera and H. zea will be of a great challenge in Brazil, mainly due to the low susceptibility to Vip3Aa20 and high genetic diversity and gene flow in both species, besides a potential of hybrid individuals between H. armigera and H. zea under field conditions.